EVALUASI PROGRAM BUDAYA MEMBACA DI SEKOLAH DASAR NEGERI - Andri Sulistyo (Kelola: Jurnal Manajemen Pendidikan, 2017)
The purpose of this study is to evaluate implementation of literacy program in Public Elementary School Tengaran (SD N Tengaran), District of Semarang. Evaluation using CIPP model. Data collection through interview, documentation, and observation with triangulation technique. The data is analyzed by description, reduction, data display and data verification. The result shows that from context aspect, students in Public Elementary School Tengaran (SD N Tengaran) need this literacy program; in input aspect, this program has answered the needs of students with support by human resources, infrastructure, budget, schedule and adequate working mechanisms; process aspect, the implementation is implemented according to plan, although there were obstacles in routine activities such as teacher’s and student’s low consistency as well as poor support from parents; and in product aspect, the result of literacy program is 90% of students have read fluently, 60% of students are confidence to do presentation, 66% of students are able to make bulletin board independently, 66% of students are able to write resume independently, 90% of students actively write their personal experience in the diary, one of 65 students passed the selection to the district level in reading poetry competition, and one student passed and get third place in speech competition in sub-district level. Based on the findings, literacy program should be continued but need improvement.